AglZ regulates adventurous (A-) motility in Myxococcus xanthus through its interaction with the cytoplasmic receptor, FrzCD - Mauriello, Emilia M.F. (2009)
Myxococcus xanthus moves by gliding motility powered by Type IV pili (S-motility) and distributed motor complexes (A-motility). The Frz chemosensory pathway controls reversals for both motility systems. However, it is unclear how the Frz pathway can communicate with these different systems. In this paper, we show that FrzCD, the Frz pathway receptor, interacts with AglZ, a protein associated with A-motility. Affinity chromatography and cross-linking experiments showed that the FrzCD-AglZ interaction occurs between the uncharacterized N-terminal region of FrzCD and the N-terminal pseudo-receiver domain of AglZ. Fluorescence microscopy showed AglZ-mCherry and FrzCD-GFP localized in clusters that occupy different positions in cells. To study the role of the Frz system in the regulation of A-motility, we constructed aglZ frzCD double mutants and aglZ frzCD pilA triple mutants. To our surprise, these mutants, predicted to show no A-motility (A(−)S(+)) or no motility at all (A(−)S(−)), respectively, showed restored A-motility. These results indicate that AglZ modulates a FrzCD activity that inhibits A-motility. We hypothesize that AglZ-FrzCD interactions are favored when cells are isolated and moving by A-motility and inhibited when S-motility predominates and A-motility is reduced.